Grazoprevir/elbasvir for the immediate treatment of recently acquired HCV genotype 1 or 4 infection in MSM. (19th April 2020) - Boyd, Anders; Miailhes, Patrick; Chas, Julie; Valantin, Marc-Antoine; Yazdanpanah, Yazdan; Rosenthal, Eric; Chevaliez, Stephane; Piroth, Lionel; Rougier, Hayette; Peytavin, Gilles; Pialoux, Gilles; Girard, Pierre-Marie; et al.
Abstract: Background: In Europe, increases in HCV infection have been observed over the last two decades in MSM, making them a key population for recently acquired HCV. Alternative combinations of direct-acting antiviral agents against early HCV infection need to be assessed. Patients and methods: In this pilot trial, MSM with recently acquired genotype 1 or 4 HCV infection were prospectively included and received 8 weeks of oral grazoprevir 100 mg and elbasvir 50 mg in a fixed-dose combination administered once daily. The primary endpoint was sustained virological response evaluated 12 weeks after the end of treatment (EOT) (SVR12). Secondary endpoints were the virological characterization of failures, the quality of life before, during and after treatment and the rate of reinfection. Results: In a 15 month period, 30 patients were enrolled, all of whom were MSM. Of the 29 patients completing follow-up, 28 (96%, 95% CI = 82%–99%) achieved SVR12. One patient interrupted follow-up (suicide) but had undetectable plasma HCV RNA at EOT. One patient with suboptimal adherence confirmed by plasma drug monitoring relapsed and developed NS3, NS5A and NS5B resistance-associated substitutions (V36M, M28V and S556G). The most common adverse events related to study drug were diarrhoea ( n  = 4, 13%), insomnia ( n  = 2, 7%) and fatigue ( n  = 2, 7%), although no patient discontinued treatment. No HIV RNA breakthrough was reported in the 28 patients with HIV coinfection. At Week 48, reinfection was diagnosed in three patients. Conclusions: Our data support the use of grazoprevir/elbasvir for immediate treatment against HCV in order to reduce HCV transmission in MSM.